Implementation of the promotion of access to Information Act in the Department of Sport, Arts and Culture in Limpopo Province - Kaka, Jermina Chuene (University of Limpopo, 2016)
The Promotion of Access to Information Act (PAIA) was approved by the South African Parliament in February 2000 and went into effect in March 2001. The Act has been introduced in both public and private sectors with the intention of implementing the constitutional right of access to information and further foster a culture of transparency and accountability in both public and private bodies by giving effect to the right to access to information. The purpose of this study was to examine the implementation process of PAIA in the Department of Sport, Arts and Culture in Limpopo Province. Using both the qualitative and quantitative approaches the study revealed that there are various factors that contribute towards non-adherence and compliance to PAIA. The main findings of the study are that, although access to information is regarded as the pillar of democracy in promoting transparency and accountability within the Department, PAIA, however, has not contributed to the improvement of access to information in the Department of Sport, Arts and Culture in Limpopo. One critical challenge the study identified is non-compliance with the requirements of the Act which is perpetuated by lack of seriousness on the part of management. The study recommends that the Department has to identify a Unit to be responsible for administering PAIA, capacitate the Unit with relevant skilled human resources and financial support. Furthermore, the study recommends that as mandated by the South African Human rights Commission, PAIA should be known to the public, staff members and stakeholders therefore awareness campaigns need to take place. Workshops and training sessions would also help in making this Act known, leading staff, people and stakeholders to use it for their benefit.
Thesis (MPA.) -- University of Limpopo,2016
Keywords: Information Act; Access to information; Public administration